Determinants of poverty levels in Indonesia: The roles of economic growth, HDI, and unemployment - Dian Prehatin; Miftakhul Choiri (Nur Science Institute, 2025)
Poverty remains a major challenge that impedes sustainable development in Indonesia. Although a range of poverty alleviation programs has been implemented, reductions in the poverty rate have not been as substantial as expected. This condition suggests that economic growth and improvements in quality of life have not fully reached vulnerable groups, highlighting the need for empirical analysis to identify the factors shaping poverty levels. This study examines the effects of economic growth, the Human Development Index (HDI), and the unemployment rate on poverty in Indonesia. The study uses a quantitative approach with secondary time-series data from 2011 to 2023 obtained from Statistics Indonesia (BPS). Multiple linear regression is applied to test the relationships among variables. The findings indicate that economic growth and unemployment do not have a statistically significant effect on poverty levels in Indonesia. In contrast, HDI has a significant effect on poverty, underscoring the importance of improving human development through education, health, and a decent standard of living as a key pathway for poverty reduction.